Proses Produksi Berita dalam Konvergensi Jurnalistik di Website Suarasurabaya.net - Puspitasari, Avit Dewi; Wulandari, E. Rizky (LPPM Stikosa-AWS, 2024)
This study aims to understand the news production process at Suarasurabaya.net online media. The results show that Suarasurabaya.net utilizes digital technology to accelerate the process of real-time news production and distribution. Features typical of online media such as hyperlinks, multimedia, and interactivity are used to package news attractively. Suarasurabaya.net also applies journalistic standards in maintaining the accuracy and credibility of information, despite facing challenges related to news speed, human resource management, and competition with other online media.